Peran Beban Kerja dan Stres Kerja terhadap Kinerja Tenaga Psikologi di Puskesmas - Rizki Maulana Hidayatullah; Finanin Nur Indana; Azzahra Rojaa Aisyah; Tiffani Hanifah Supriyanti (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
Psychology personnel in primary healthcare centers (Puskesmas) play a strategic role in delivering mental health services at the primary level; however, they are frequently confronted with complex and multifaceted job demands. This study aims to examine the effects of workload and work stress on the job performance of psychology personnel in Puskesmas in Surabaya City. A quantitative approach with a correlational cross-sectional design was employed. The study population comprised all psychology personnel working in Puskesmas in Surabaya City, with total sampling applied, resulting in 63 respondents. Workload and work stress were measured using five-point Likert scales, while job performance was assessed based on monthly psychology service reports. Data were analyzed using multiple linear regression analysis. The results indicate that the majority of psychology personnel experienced high workload levels and relatively high work stress, whereas overall job performance was predominantly categorized as good. Regression analysis revealed that workload and work stress simultaneously had a significant effect on job performance, and partially both variables exerted a negative effect on performance. These findings suggest that although psychology personnel are generally able to maintain adequate performance, excessive workload and elevated work stress may potentially undermine performance in the long term if not properly managed. Therefore, this study highlights the importance of systematic workload management and work stress intervention strategies to sustain the quality of psychological services in primary healthcare settings.